Sebaceous Carcinoma with Widespread Metastases: A Case Report - Ningthoujam Dinita Devi; Rahul Mahawar; Sarmila Longjam; Laishram Singh; Haobijam Persy (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Sebaceous carcinoma (SC) is an infrequently encountered skin malignancy noted for its aggressive nature. We report here a 78-year-old male who presented to the Department of Radiation Oncology at RIMS Imphal with a two-month history of painless ulcerated swellings on the scalp, right ring finger, right big toe, and upper back, each measuring approximately 2x2cm2 with erythematous discoloration, hard, tender and adherent to the underlying structures. The histopathological study confirmed the lesion as sebaceous carcinoma. Palliative radiotherapy was administered. The patient responded favorably to the prescribed treatment regimen, resulting in a substantial 50% reduction in tumor size.Consequently, regular follow-up monitoring was strongly recommended to ensure continued progress and optimal patient condition management. Early detection of this tumor is imperative for improved prognosis and outcomes. Despite this, the prognosis remains poor due to the high local recurrence rates and distant metastasis.